PENGARUH METODE GAMIFIKASI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN KETERLIBATAN SISWA PADA KELAS IV DI SDN 50 PONTIANAK BARAT TAHUN PELAJARAN 2025/2026 - Tri Agrizki Nur Khofifah; M. Alias; Yusida Imran (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the gamification method on students’ engagement in Islamic Education learning in grade IV at SDN 50 Pontianak Barat. This research uses a quantitative approach with a quasi-experimental design. Data were collected through questionnaires, observation, and documentation, and analyzed using simple linear regression. The results show that the implementation of the gamification method is in a high category with an average score of 36.76. Student engagement increased in behavioral, emotional, and cognitive aspects, indicated by higher activeness, enthusiasm, and understanding. The hypothesis test results show a significance value of 0.000 < 0.05, indicating a significant effect of the gamification method on student engagement. Furthermore, gamification was more effective than conventional methods based on the improvement of posttest scores in the experimental class. Therefore, the gamification method has a positive effect on students’ engagement in Islamic Education learning.